2008
DOI: 10.1007/s00404-008-0593-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida albicans and bacterial vaginosis in asymptomatic pregnant women in South Yorkshire, United Kingdom

Abstract: Prevalence of Candida albicans and bacteria vaginosis among asymptomatic pregnant women was 12.5 and 3.54%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
16
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
9
16
2
3
Order By: Relevance
“…These findings are consistent with those previously reported from other countries as Germany (Mendling and Brasch, 2012), Italy (Consolaro et al, 2004), India (Jindal et al, 2006(Jindal et al, , 2007Ahmad and Khan, 2009), Australia (Pirotta and Garland, 2006) and Nigeria (Nwadioha et al, 2010), as well as, Saudi Arabia (Al-Hedaithy, 2002). Our results also indicated that Candida positive culture was significantly correlated with pregnancy (P=0.047), the increased number (malt-parity) of pregnancy (P=0.001), as well as women-child bearing age of (40-45 years versus same age but non-pregnant (P=0.026) which confirms previous findings by Akinbiyi et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with those previously reported from other countries as Germany (Mendling and Brasch, 2012), Italy (Consolaro et al, 2004), India (Jindal et al, 2006(Jindal et al, , 2007Ahmad and Khan, 2009), Australia (Pirotta and Garland, 2006) and Nigeria (Nwadioha et al, 2010), as well as, Saudi Arabia (Al-Hedaithy, 2002). Our results also indicated that Candida positive culture was significantly correlated with pregnancy (P=0.047), the increased number (malt-parity) of pregnancy (P=0.001), as well as women-child bearing age of (40-45 years versus same age but non-pregnant (P=0.026) which confirms previous findings by Akinbiyi et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…Analysis revealed significant association of the detection rate of vulvovaginal candidiasis with the subject age groups as it was parallel to reported results of Akinbiyi et al which mentioned age distribution of vulvovaginal candidiasis rate is around childbearing period [5]. It has been found that different kinds of contraception could be a risk factor for vulvovaginal candidiasis infection as others demonstrated it.…”
Section: Discussionsupporting
confidence: 79%
“…However, none or just one of these symptoms may observe in vulvovaginal candidiasis. Moreover mixed infections (Bacterial, Trichomonas besides Candida) of most patients lead to misdiagnosis and therapy failures [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The acidity level of the vagina is maintained at pH 4.0-4.5. However, any physiological changes that affect the beneficial bacteria in the vagina would alter the acidity of the vagina reducing its pH to 5.0-6.5 therefore enhancing the establishment of pathogenic organisms such as Candida [2,20]. Vaginal pH may increase with age, phase of menstrual cycle, sexual activity, contraception choice, pregnancy, and use of antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%